Robust gain-scheduling 9-∞ control of uncertain continuous-time systems having magnitude- and rate-bounded actuators: An application of full block S-procedure - Kucukdemiral, Ibrahim B.; Yazici, Hakan (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
This paper addresses a novel robust gain-scheduling(GS) state-feedback (SF) H-infinity (induced L-2 ) control method for uncertain continuous-time(CT) systems having actuators with hard rate and magnitude bounds. The proposed method relies on acceleration form representation of the uncertain CT system. The technique enables the user to represent the control signal and its slew rate as auxiliary outputs along with the main controlled output. Two different norms, namely the induced L-infinity and L-2 are used to control the system effectively. While the L-infinity gain from the exogenous disturbance inputs to the control signal related outputs is used to deal with actuator saturation problem, L-2 gain from the disturbance inputs to the performance outputs is utilised in attenuation of the effects of the disturbances. To achieve these goals with minimal conservatism, we develop new forms of dilated Matrix Inequality (MI) conditions for peak-to-peak gain and L-2 gain with no additional conservatism. Then, we propose a novel robust GS control methodology to deal with the problem via dilated MIs and a modified full block S-procedure method (MFBSPM). The utilisation of MFBSPM ensures that the robust control design method of this note applies to any uncertain system having rational parameter dependence. Finally, the efficiency of the presented method is portrayed through extensive simulations of the responses of a marine vessel to-wave excitations in which the vessel model is assumed to have magnitude and rate limited active fin stabiliser. (c) 2021 The Franklin Institute. Published by Elsevier Ltd. All rights reserved.
Keywords: LINEAR-SYSTEMS; TRACKING CONTROL; STABILITY ANALYSIS; NONLINEAR-SYSTEMS; NANO-MANIPULATOR; DESIGN METHOD; STABILIZATION; ANTIWINDUP; SATURATION; SUBJECT; Automation & Control Systems; Engineering; Mathematics